In-Person and Remote Workshops for People With Neurocognitive Disorders: Recommendations From a Delphi Panel - Manera, Valeria; Agüera-Ortiz, Luis; Askenazy, Florence; Dubois, Bruno; Corveleyn, Xavier; Cross, Liam; Febvre-Richards, Emma; Fabre, Roxane; Fernandez, Nathalie; Foulon, Pierre; Gros, Auriane; Gueyraud, Cedric; et al. (Frontiers in Aging Neuroscience, 2022)
Workshops using arts and board games are forms of non-pharmacological intervention widely employed in seniors with neurocognitive disorders. However, clear guidelines on how to conduct these workshops are missing. The objective of the Art and Game project (AGAP) was to draft recommendations on the structure and content of workshops for elderly people with neurocognitive disorders and healthy seniors, with a particular focus on remote/hybrid workshops, in which at least a part of the participants is connected remotely. Recommendations were gathered using a Delphi methodology. The expert panel (N= 18) included experts in the health, art and/or board games domains. They answered questions via two rounds of web-surveys, and then discussed the results in a plenary meeting. Some of the questions were also shared with the general public (N=101). Both the experts and the general public suggested that organizing workshops in a hybrid format (some face-to-face sessions, some virtual session) is feasible and interesting for people with neurocognitive disorders. We reported guidelines on the overall structure of workshops, practical tips on how to organize remote workshops, and a SWOT analysis of the use of remote/hybrid workshops. The guidelines may be employed by clinicians to decide, based on their needs and constraints, what interventions and what kind of workshop format to employ, as well as by researchers to standardize procedures to assess the effectiveness of non-pharmacological treatments for people with neurocognitive disorders.